Tinjauan Hukum Terhadap Wanprestasi dalam Kasus Gagal Bayar pada Platform Fintech Lending Berdasarkan Peraturan Otoritas Jasa Keuangan No. 77/POJK.01/2016 : Studi Kasus PT. Crowde Membangun Bangsa - Muhammad Bima Nafis Mulki; Temmy Fitriah Alfiany (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The purpose of this study is to determine how the regulation and implementation of legal protection for lenders in cases of default based on the Financial Services Authority Regulation (POJK) No. 77/POJK.01/2016 concerning Information Technology-Based Money Lending Services. This study also examines the form of legal responsibility of the platform organizer, as well as dispute resolution efforts that can be taken by lenders. The research method used is the normative legal method with a statutory regulatory approach and case studies. Data were obtained through literature studies and documentation of applicable legal provisions, as well as relevant documents and reports from PT. Crowde. The analysis was carried out qualitatively-descriptively to assess the suitability between field practices and applicable regulations. The results of the study indicate that POJK No. 77/POJK.01/2016 has not fully provided comprehensive legal protection for lenders in cases of default. Legal responsibility for default is still largely borne by the civil relationship between the borrower and the lender, without any concrete risk recovery mechanism from the organizer. Therefore, it is necessary to strengthen regulations, increase platform transparency, and play an active role for the OJK and the Indonesian Joint Funding Fintech Association (AFPI) in supervising and following up on default cases.